The pandemic of 2019 novel coronavirus infection and Hajj 2021 - Behroz Mahdavi Poor; Jalil Rashedi; Nazila Gheitarani; Mohammad Asgharzadeh (Archives of Preventive Medicine - Peertechz Publications, 2020)
In December 2019, an outbreak of severe pneumonia of anonymous etiology was reported from Wuhan city, China. The Chinese health authorities rapidly determined the causative agent of the disease as a novel coronavirus (2019-nCoV) [1]. Coronavirus Disease 2019 (COVID-19) quickly widespread and becomes a major public health concern throughout the world. Growing evidences, including transmission of the infection among family members and infection of the hospital workers revealed the ability of the emerging virus to transmit continuously from human-to-human [1,2].